Perceived Outdoor Activity Constraints and Negotiation Strategies in Greenville, NC - Frost, Andrew (East Carolina University, 2017)
Individuals sometimes fail to participate in outdoor activities—to the detriment of their health—as a result of leisure constraints. Constraints are pressures individuals feel when attempting to participate in different activities that limit their full participation. Research suggests all individuals perceive constraints in some form whether they participate or not. The purpose of this study was to determine if there is a relationship between leisure constraints and frequency of participation among individuals and more specifically among different socio-demographic groups in Greenville, North Carolina. Additionally, this study explored which constraint negotiation and agency facilitation strategies have the potential to increase participation frequency in outdoor recreation activities according to respondents’ socio-demographic characteristics in Greenville, NC. This thesis accomplishes the aforementioned work by conducting a quantitative survey administered via U.S. mail, door-to-door intercepts and face-to-face intercepts. The survey results suggest that despite a high frequency of participation and lower levels of constraints, agency facilitation and negotiation strategies exist that could be used to increase outdoor activity involvement.
Keywords: leisure constraints; constraints; negotiations; facilitation strategies; outdoor activities